Friction of fluoroplastic with steel in a hydraulic fluid medium when transient mode - Alisin Valery (E3S Web of Conferences, 2024)
The article considers the issues of experimental research of the antifriction properties of fluoroplastic seals of piston pump hydraulic systems in a transient friction mode. The statement about the influence of frictional heating on the tribological properties of the seal is substantiated. Model experiments are used to study the friction coefficients at the moment of changing the direction of the contacting surfaces movement and the transient period from the moment of starting from a standstill to the steadystate friction mode. The experiments were carried out under conditions of heating the hydraulic fluid to the maximum temperature. Particular attention is paid to the change in the friction coefficient with increasing load-speed characteristics. The limiting contact pressures that ensure trouble-free operation of a seal made of radiation-modified fluoroplastic have been determined.